2018
DOI: 10.3382/ps/pey290
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic of guinea fowl (Numida meleagris) farming in Ivory Coast

Abstract: In order to promote farming of guinea fowl and to diversify the sources of income of Ivorian farmers, a survey was conducted in 2016 in 15 regions (197 farmers) out of a total of 31 regions in Ivory Coast. The aims were 1) to establish a better knowledge of guinea fowl farming; 2) to assess the level of technical knowledge of farmers; and 3) to establish a global typology of farmers based on their socio-economic profile, the goal of the farming (sale or consumption), and their level of technical knowledge. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
2
8
0
2
Order By: Relevance
“…This instinct, which is not very malleable constitutes a major constraint for the women in its production. This finding aligns with the earlier studies carried out in Ivory Coast ( Kone et al., 2018 ; Kouassi et al., 2019 ); Burkina-Faso ( Traore et al., 2018 ) and Ghana ( Avornyo et al., 2016 ; Abdul-Rahman and Adu, 2017 ) that found that guinea fowl farmers were predominantly men. Similar findings were reported in Togo ( Soara et al., 2020 ), Niger ( Moussa Amadou et al., 2010 ) and Zimbabwe ( Kusina et al., 2012 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This instinct, which is not very malleable constitutes a major constraint for the women in its production. This finding aligns with the earlier studies carried out in Ivory Coast ( Kone et al., 2018 ; Kouassi et al., 2019 ); Burkina-Faso ( Traore et al., 2018 ) and Ghana ( Avornyo et al., 2016 ; Abdul-Rahman and Adu, 2017 ) that found that guinea fowl farmers were predominantly men. Similar findings were reported in Togo ( Soara et al., 2020 ), Niger ( Moussa Amadou et al., 2010 ) and Zimbabwe ( Kusina et al., 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…This same observation is common in most African countries. The study therefore emphasized the design and translation of technical manuals into local language due to the farmers' low level of formal education ( Kone et al., 2018 ; Traore et al., 2018 ; Kouassi et al., 2019 ) as this will facilitate better understanding of the birds management requirement and subsequently lead to a sustainable development of this sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En México, por ejemplo, estas aves tienen un rol importante en la mejora de la alimentación de los campesinos al proveerles alimentos de buena calidad nutricional, siendo la carne el producto de mayor importancia (Gutiérrez-Triay et al, 2007). Las aves mayormente utilizadas son las gallinas y los guajolotes (Juárez y Gutiérrez, 2009;Itza-Ortiz et al, 2016); sin embargo, debido al creciente aumento de la población humana, existe un déficit de alimentos proteicos de origen animal, por lo cual es necesario diversificar las especies avícolas criadas para este fin. Una alternativa biológica y económicamente viable es la gallina de Guinea (Numida meleagris), ave nativa del continente africano, en donde su carne es apreciada como una fuente importante de proteína animal, por lo que es ampliamente consumida por las familias locales (Ebegbulem, 2018).…”
Section: Introductionunclassified
“…La crianza de N. meleagris tiene ventajas considerables; por ejemplo, las aves se adaptan a diversas condiciones agroclimáticas, consumen una gran variedad de alimentos no convencionales, tienen la capacidad de protegerse ante depredadores, controlan las garrapatas y otras plagas, son tolerantes a la mayoría de las enfermedades comunes de las aves de corral y no se requiere demasiada mano de obra e infraestructura costosa para su manejo (Ebegbulem, 2018;Koné et al, 2018;Musundire et al, 2018). Productivamente, la gallina de Guinea también presenta buena ganancia de peso, conversión alimenticia (Houndonougbo et al, 2017;Eleroğlu et al, 2018) y rendimiento de la canal (Mareko et al, 2006;Chiroque et al, 2018), aun cuando es comparado con el rendimiento de la canal del pollo (Musundire et al, 2018).…”
Section: Introductionunclassified